The KDM5B and KDM1A lysine demethylases cooperate in regulating androgen receptor expression and signalling in prostate cancer - Metzler, Veronika M.; de Brot, Simone; Haigh, Daisy B.; Woodcock, Corinne L.; Lothion-Roy, Jennifer; Harris, Anna E.; Nilsson, Emeli M.; Ntekim, Atara; Persson, Jenny L.; Robinson, Brian D.; Khani, Francesca; Laursen, Kristian B.; et al. (Frontiers in Cell and Developmental Biology, 2023)
Histone H3 lysine 4 (H3K4) methylation is key epigenetic mark associated with active transcription and is a substrate for the KDM1A/LSD1 and KDM5B/JARID1B lysine demethylases. KDM1A is an amine oxidase that can act to repress or enhance transcriptional activation by demethylating di- and tri- methylated H3K4 as part of the NURD repressive complex, or H3K9 methylation in cooperation with the androgen receptor (AR). In contrast, KDM5B/JARID1B is a 2-oxoglutarate and Fe(2+) dependent oxygenase that demethylates the di- and tri-methylated histone H3 lysine 4 (H3K3) generally associated with transcriptional activation. Increased expression of KDM1A and KDM5B is implicated in many cancer types, including prostate cancer. Both KDM1A and KDM5B have been shown to interact with AR and to promote androgen regulated gene expression. For this reason, there is great interested in the development of new therapies targeting KDM1A and KDM5B, particularly in the context of castrate resistant prostate cancer, where conventional androgen deprivation therapies and androgen receptor signalling inhibitors are no longer effective. While the contribution of KDM1A to prostate cancer is well established, KDM5B is less well understood. However, there is evidence that KDM5B is implicated in numerous pro-oncogenic mechanisms in many different types of cancer, including the hypoxic response, immune evasion and PI3/AKT signalling. Here we elucidate the cooperative functions of KDM1A and KDM5B in prostate cancer. We show that KDM5B mRNA and protein expression is elevated in prostate adenocarcinoma and advanced tumors. We show that knockdown of KDM5B and the CPI-455 KDM5B inhibitor impairs androgen regulated transcription and splicing. Using KDM1A (Namoline) and KDM5B (CPI455) selective pharmaco-inhibitors, we show that KDM1A and KDM5B individually regulate androgen regulated transcription and cooperate to regulate AR expression. We demonstrate that combined inhibition of KDM1A and KDM5B impairs prostate cancer cell proliferation and invasion more than individual inhibition of KDM1A and KDM5B. The cooperative functions of KDM1A and KDM5B in the regulation of AR expression and function provide a novel target for PCa therapy, especially for the hard-to-treat castrate resistant prostate cancer.